2022
DOI: 10.1038/s41467-022-34522-z
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-enhanced tough, resilient and adhesive eutectogels for highly reliable strain/pressure sensing under extreme conditions

Abstract: Natural gels and biomimetic hydrogel materials have been able to achieve outstanding integrated mechanical properties due to the gain of natural biological structures. However, nearly every natural biological structure relies on water as solvents or carriers, which limits the possibility in extreme conditions, such as sub-zero temperatures and long-term application. Here, peptide-enhanced eutectic gels were synthesized by introducing α-helical “molecular spring” structure into deep eutectic solvent. The gel ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…2(h)), respectively, and the lower residual strain indicated the potent crosslinking points in the hydrogel network and stable mechanical properties. 53,54 Moreover, it was found that the dissipated energy was continuously elevated from 3.05 to 63.16 kJ m −3 with the strain gradually increasing from 100% to 700% (Fig. 2(i)), which was attributed to the partial dissociation of reversible non-covalent interactions during deformation.…”
Section: Resultsmentioning
confidence: 94%
“…2(h)), respectively, and the lower residual strain indicated the potent crosslinking points in the hydrogel network and stable mechanical properties. 53,54 Moreover, it was found that the dissipated energy was continuously elevated from 3.05 to 63.16 kJ m −3 with the strain gradually increasing from 100% to 700% (Fig. 2(i)), which was attributed to the partial dissociation of reversible non-covalent interactions during deformation.…”
Section: Resultsmentioning
confidence: 94%
“…More importantly, unlike other stimuli-responsive polymers, the peptide segments fold back into α-helix in a highly precise way. In such a structure, the amino acid residues are arranged so that intramolecular hydrogen bonds could form between the oxygen of the CO of amino acid residue i and the hydrogen of the N–H group of the bond four amino acid residues below it in the helix ( i + 4). For this reason, the newly formed helical structure is almost identical to the original one. Therefore, the shape of the imprint cavities could be largely restored.…”
Section: Results and Discussionmentioning
confidence: 99%
“…HEAD gels outperformed the majority of known natural polymers as well as synthetic hydrogels in their comprehensive mechanical performance (Fig. 5b) 3,6,13,14,16,18,[39][40][41][42][43] . For example, HEAD gels could reach a comparable toughness as spider silk, but was 40 times more flexible.…”
Section: Robustness Tunability Self-healing and Underwater Stabilitymentioning
confidence: 95%
“…To address the issue, a number of approaches have been proposed. One popular idea is to incorporate tensile-resistant units into hydrogel, such as micellar crosslinkers 3,13 , force responsive groups 4 , peptide crosslinkers 14 , covalent organic frameworks 15 , and ionic crosslinking points that are usually found in double network hydrogels 16,17 . During structural deformation, the tensileresistant units are subject to quick chemical changes, which absorbs energy and converts into a more extended state.…”
mentioning
confidence: 99%